The Milk Metabolome of Non-secretor and Lewis Negative Mothers - Wang, Aidong; Koleva, Petya; du Toit, Elloise; Geddes, Donna T.; Munblit, Daniel; Prescott, Susan L.; Eggesbø, Merete; Johnson, Christine C.; Wegienka, Ganesa; Shimojo, Naoki; Campbell, Dianne; Kozyrskyj, Anita L.; et al. (Frontiers in Nutrition, 2021)
Introduction: The functional role of milk for the developing neonate is an area of great interest, and a significant amount of research has been done. However, a lot of work remains to fully understand the complexities of milk, and the variations imposed through genetics. It has previously been shown that both secretor (Se) and Lewis blood type (Le) status impacts the human milk oligosaccharide (HMO) content of human milk. While some studies have compared the non-HMO milk metabolome of Se+ and Se- women, none have reported on the non-HMO milk metabolome of Se- and Le- mothers. Method and results: To determine the differences in the non-HMO milk metabolome between Se-Le- mothers and other HMO phenotypes (Se+Le+, Se+Le-, and Se-Le+), 10 milk samples from 10 lactating mothers were analyzed using nuclear magnetic resonance (NMR) spectroscopy. Se or Le HMO phenotypes were assigned based on the presence and absence of 6 HMOs generated by the Se and Le genes. After classification, 58 milk metabolites were compared among the HMO phenotypes. Principal component analysis (PCA) identified clear separation between Se-Le- milk and the other milks. Fold change analysis demonstrated that the Se-Le- milk had major differences in free fatty acids, free amino acids, and metabolites related to energy metabolism. Conclusion: The results of this brief research report suggest that the milk metabolome of mothers with the Se-Le- phenotype differs in its non-HMO metabolite composition from mothers with other HMO phenotypes.